Livro de imagem como instrumento para o ensino-aprendizagem de Libras por visuais (surdos) no período tardio de aquisição da Libras - Barbosa, Adriana Pereira (2022)
This research was conceived from an investigation and dialogue with visual persons (deaf) residing in the city of Poxoréo/MT, without the contact of the Brazilian Sign Lan- guage -Libras in the family and school contexts. Considering language as a mediating instrument in the construction of the subject with the Other, in a process of interaction and alterity, the objective of this research was to provide opportunities for the visuals of this municipality who had late contact with Libras, a teaching-learning workshop of this language. Thus, the proposal was to use the picture book as a teaching tool. This study aims to answer the following question: how can the picture book contribute to the learning of Libras by the visual person in the late contact of L1? To support the research, we assumed the enunciative-discursive conception of language, according to the theoretical framework of the Bakhtin Circle (1929) and the concept of interaction in the teaching-learning process according to Vygotsky (1934). When referring to the person with deafness, we use the terminology visual person, according to Duarte (2016). The methodological approach is qualitative, exploratory, descriptive and inter- pretative. The methodology is of the case research type. To obtain the records, video recording and interviews with the participants were carried out. The research locus was the municipality of Poxoréo, with three visual participants, one of the participants learn- ing Libras with peers in the immediate need for communication, and the other two par- ticipants had their first contact with the formal teaching of Libras during this research. The analysis of the results shows that the picture book serves as a scaffolding for the teaching of Libras, mediated by a more advanced pair, composing one of the possible teaching strategies according to the linguistic needs of visual persons.